A formação e o trabalho do professor de Geografia para os egressos do PIBID no estado do Paraná (2010-2017) - Woitowicz, Eliete (2021)
In this research, it seek to analyze the contributions and limitation of the Institutional Scholarship Program Initiation to Teaching (PIBID) in the formation of the teaching practice in Geography. The focus of the analysis was based on the graduates that attended the Degree in Geography in the Public University Education Institute (IES) in Parana State, especially in relation to graduates that are practicing the profession, above all, in Basic Education. The considered period to the research development goes from 2010 to 2017, due to the beginning of actions of Geography degree Program (2010). Therefore, it can take into account that in 2017 to meet the publication of the new PIBID notice, realized by the Education Ministry (MEC) in 2018. According to the proposed regulation in published notice between 2010 to 2017, it tries to understand how to occur the implementation of the PIBID in the teachers initial formation, into to the Geography degree course. The didactic-pedagogical relation established by the PIBID in Basic Education School, Beginner Geography teachers related them. This way, it seek to understand what way the formative activities of PIBID contribute to specific knowledge learning of School Geography, from the perspective of the program graduates. For that, the methodology used to develop to this research was based on the quanti-qualitative approach, by case study, with participation to 83 PIBID graduates in Geography. Of this total, 75 graduates participated in the survey, through a semi-open questionnaire sent online. The respective participants that graduated degree in public IES in Parana State between 2010 to 2017 and, they answered the questionnaire by the period from July/2018 to April/2019. In addition to the mentioned people, 08 PIBID graduates in geography were interviewed by WhatsApp who they represent one PIBID graduate in each public IES of Parana State. The interviewees have taught in the Basic Education at the interview moment, that it occurred between March to April of 2020. It was verified that PIBID actions articulate the school and graduated knowledge during the Degree that favor the learning of the teaching knowledge and the specific knowledge in school geography. This way, the graduates who were teaching they claimed that got to link between what they learned in PIBID to the classroom that they teach as beginner teachers. Besides, the program stimulates the practice of the research, mainly aspects relative to the Geography teaching. It expects that the obtained results contribute with the initial training of Geography teachers, with the to the PIBID continues and its expansion in the public participants universities and schools, meeting the particularities of each institution and region.